Android App for Meter Reading (International Journal of Engineering and Computer Science, 2015)
There exist a billing process for meter reading of electricity, gas and water supplier companies, as well as to know the consumption of particular vehicle by reading the meter. Now a days, electricity billing and meter reading are very complex tasks. The current method of billing process uses manual work of reading the meter, updating details of meter and sending bill to the customer. We are developing the technology that comprises android application as well as web application to get reading, updating information into server and informing consumers about electricity consumption units and bill amount. To make meter reading task automatic android application is used to get the readings from the meter by only capturing the image of the meter and then performing the OCR i.e. ”optical character recognition” technique on that image in android app. The result of OCR is meter readings extracted from the captured image and then send to the server. With the help of web application customer can receive mail regarding the bill at the instant the image is accepted at the server and then customer can view his bill. New features can also be added that will reduce workload on companies as well as their workers.